Association between normal tension glaucoma and the risk of Alzheimer's disease: a nationwide population-based cohort study in Taiwan. Issue 11 (5th November 2018) - Chen, Yu-Yen; Lai, Yun-Ju; Yen, Yung-Feng; Shen, Ying-Cheng; Wang, Chun-Yuan; Liang, Chiao-Ying; Lin, Keng-Hung; Fan, Lir-Wan
Abstract : Objectives: To investigate a possible association between normal tension glaucoma (NTG) and an increased risk of developing Alzheimer's disease (AD). Design: Retrospective cohort study. Setting: NTG group and the comparison group were retrieved from the whole population of the Taiwan National Health Insurance Research Database from 1 January 2001 to 31 December 2013. Participants: A total of 15 317 subjects with NTG were enrolled in the NTG group, and 61 268 age-matched and gender-matched subjects without glaucoma were enrolled in the comparison group. Primary and secondary outcome measures: Kaplan-Meier curves were generated to compare the cumulative hazard of AD between the two groups. A multivariable Cox regression analysis was used to estimate the adjusted hazard ratios (HRs) of AD, adjusted for diabetes, hypertension, hyperlipidaemia, coronary artery disease and stroke. Furthermore, risk factors for developing AD among the NTG group were investigated. Results: The mean age of the cohort was 62.1±12.5 years. Patients with NTG had significantly higher proportions of diabetes, hypertension, hyperlipidaemia, coronary artery disease and stroke than the comparisons. Patients with NTG had a significantly higher cumulative hazard for AD than the comparisons (p<0.0001). In the multivariable Cox regression after adjustment for confounders, the NTG group had a significantly higher risk of AD (adjusted HR 1.52; 95% CI 1.41 to 1.63). Moreover, in the NTG group, when we compared the effects of different types of glaucoma eye drops, none of the eye drops used were significant risk factors or protective factors for AD. Conclusions: People with NTG are at a significantly greater risk of developing AD compared with individuals without glaucoma. Among patients with NTG, none of the glaucoma eye drops used significantly changed the risk of subsequent AD.